Analisis Sistem Surveilans Hipertensi di Puskesmas Bantar Kota Tasikmalaya tahun 2024 - Alzena Kevina Shahla; Natasya Hairunnisa; Syalsabila Pulungan; Marshanda Darianti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Hypertension is one of the non-communicable diseases (NCDs) with a high incidence rate and significant impact on public health, including in the working area of Bantar Public Health Center, Tasikmalaya City. This study aims to evaluate the implementation of hypertension surveillance at Bantar Health Center in 2024. The research employed a mixed-method approach with a descriptive-exploratory design through document review and in-depth interviews with program implementers. The results indicate that the surveillance process has been carried out systematically through screenings at Posyandu and Posbindu, data processing using the ePus and SIPTM applications, and tiered reporting to the Health Office. In 2024, a total of 1,559 hypertension cases were recorded, predominantly affecting women (74%) and individuals of productive age. Challenges encountered include limited human resources, low community participation, and technical issues with the applications. These findings highlight the importance of strengthening cadre capacity, providing flexible screening schedules, and enhancing digital and cross-sectoral support. Hypertension surveillance plays a vital role in evidence-based NCD control and more targeted health interventions.